Axillary reverse mapping in breast cancer: A Canadian experience. Issue 7 (23rd July 2014) - Kuusk, Urve; Seyednejad, Nazgol; McKevitt, Elaine C.; Dingee, Carol K.; Wiseman, Sam M.
<x xml:space="preserve">Abstract</x> Background The aim of this study was to evaluate the axillary reverse lymphatic mapping (ARM) procedure for reducing the risk of arm lymphedema after breast cancer surgery. Methods The ARM procedure was carried out with a subareolar injection of technetium‐99 sulfur colloid the morning of surgery, and a patent blue dye injection into the upper inner arm after anesthesia. Results Fifty‐two women made up our study population. Thirty‐seven patients underwent sentinel lymph node biopsy (SLNB) and 15 patients underwent an axillary lymph node dissection (ALND) for known nodal metastasis. The sentinel lymph node was identified in 36 of the 37 cases who underwent SLNB alone and in 12 of 15 patients who underwent on ALND. In 13 patients, both blue and radioactive lymph nodes or lymphatics were clearly identified (25%) and 5 patients had a clear crossover with nodes being both blue and hot. Only a single patient with crossover lymphatics had metastases present in their sentinel node. Conclusion The ARM technique did not prevent identification of the SLN and we identified much greater crossover than reported. We had a single patient, who underwent a sentinel node biopsy, with mild arm lymphedema (1.9%) after 2 years of follow up. J. Surg. Oncol. 2014 110:791–795. © 2014 Wiley Periodicals, Inc.